Mfd as a central partner of transcription coupled repair - Monnet, Jordan (Landes Bioscience, 2013)
Transcription-coupled repair (TCR) is one of the key of the nucleotide excision repair (NER) pathways required to preserve genome integrity. Although understanding TCR is still a major challenge, recent single-molecule experiments have brought new insights into the initial steps of TCR leading to new perspectives.